2021
DOI: 10.1142/s0218539321500327
|View full text |Cite
|
Sign up to set email alerts
|

A Logistic Growth Model for Software Reliability Estimation Considering Uncertain Factors

Abstract: Software reliability growth models (SRGMs) are widely used to estimate software reliability by analyzing failure dataset throughout the testing process. A large number of SRGMs have been proposed on a regular basis by researchers since the 1970s. They are represented with a set of assumptions and a set of parameters. One major problem in SRGMs is that the uncertainties surrounding the assumptions and parameters are generally not taken into account by most of them. Therefore, sometimes, the predicted reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…(2006), Chakravarty (2007), Shaik and Akthar (2011), Gandhi et.al. (2019, and very recently Yaghoobi (2021) as well as Haque & Ahmad (2021). Most (if not all) research we found focused on how good a model can fit in predicting the growth of the software reliability.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…(2006), Chakravarty (2007), Shaik and Akthar (2011), Gandhi et.al. (2019, and very recently Yaghoobi (2021) as well as Haque & Ahmad (2021). Most (if not all) research we found focused on how good a model can fit in predicting the growth of the software reliability.…”
Section: Literature Reviewmentioning
confidence: 86%
“…(1997), Satoh & Yamada (2002), Pham (2005), Rafi et.al. (2010, Zang & Pi (2018), and finally Haque & Ahmad (2021) clearly demonstrate that this model is widely researched and used.…”
Section: Logistic Diffusion Model In Srgmmentioning
confidence: 86%
“…Triambak S. used logistic growth model to predict COVID-19 mortality [6], Asraful Haque Md. used logistic growth model to analyze software reliability under uncertain factors [7], and Abdul Latif Nurul Syaza used the logistic growth model to establish agricultural management strategies [8].…”
Section: Logistic Growth Modelmentioning
confidence: 99%
“…Because software is used in many different ways, its roles have become very diverse, and the environment provided to each piece of software has also become very diverse. Many studies have been conducted on SRMs that assume uncertainty in operating environments [17][18][19][20][21][22][23][24][25][26]. Here, uncertain operating environments refer to the environments used by actual consumers.…”
Section: Introductionmentioning
confidence: 99%
“…To assume uncertain operating environments, Teng and Pham [18] and Pham [19] proposed an SRM utilizing a gamma distribution, and Song et al [20] assumed the uncertain operating environments to be exponential and applied the failure detection rate function as a monotonically increasing function to present a new model for uncertain operating environments. Many researchers have proposed an SRM that considers uncertain factors [21][22][23][24]. Chang et al [25] proposed an SRM that considers testing coverage, which indicates whether sufficient tests have been performed in uncertain operating environments.…”
Section: Introductionmentioning
confidence: 99%